Does Comprehensive Geriatric Assessment Reduce the Incidence of Postoperative Delirium? A Quasi-experimental Study in Older Adults Undergoing Transcatheter Aortic Valve Implantation - Schwesinger A; Tsai LT; Lang W; Mantegazza N; Bauernschmitt R; Wilhelm MJ; Bischoff-Ferrari HA; Gagesch M (Clinical Interventions in Aging, 2024)
Anna Schwesinger,1,* Li-Tang Tsai,1,* Wei Lang,1 Noemi Mantegazza,1 Robert Bauernschmitt,2 Markus Johannes Wilhelm,2 Heike Annette Bischoff-Ferrari,1,3,4 Michael Gagesch1,5,6 1Center on Aging and Mobility, University of Zurich, Zurich, Switzerland; 2Clinic for Cardiac Surgery, University Hospital Zurich, Zurich, Switzerland; 3Department of Geriatrics and Aging Research, University of Zurich, Zurich, Switzerland; 4IHU HealthAge, University Hospital Toulouse and University Toulouse III Paul Sabatier, Toulouse, France; 5Department of Aging Medicine, University Hospital Zurich, Zurich, Switzerland; 6University Clinic of Aging Medicine, Zurich City Hospital, Zurich, Switzerland*These authors contributed equally to this workCorrespondence: Michael Gagesch, University Clinic for Aging Medicine, Zurich City Hospital, Tièchestrasse 99, 8037 Zürich, Switzerland, Tel +41 44 417 31 98, Email michael.gagesch@stadtspital.chPurpose: Postoperative delirium (POD) after transcatheter aortic valve implantation (TAVI) is frequent in older adults and associated with multiple negative outcomes including a higher mortality. We aimed to investigate whether a comprehensive geriatric assessment (CGA) prior to TAVI reduces the odds of POD and results in a positive change in self-care ability, intended to lay a foundation for future geriatric comanagement.Patients and methods: We used a retrospective, single-center study with a quasi-experimental design enrolling patients aged 70 years and older undergoing CGA before elective TAVI, and a nonrandomized comparison group without preoperative CGA. Data on POD occurrence during the first 5 days after TAVI (primary outcome) and change in self-care ability index (SPI) between admission and discharge (secondary outcome) were collected from electronic health records and CGA data (exposure) by clinical assessment. To explore associations between (1) CGA and POD, and (2) CGA and SPI, multivariate logistic regression and linear regression models were applied adjusting for age, sex, BMI, and number of medications.Results: Among 435 patients (mean age 81.0 ± 5.6 years, 43.6% women, median [IQR] SPI at baseline 40 [39, 40] points), POD incidence was 14.3% in the CGA group vs 18.8% in the non-CGA group (P 0.219). Undergoing CGA before TAVI was not associated with the odds for POD (OR: 1.15; 95%CI: 0.65– 2.04) or improved SPI (P 0.073).Conclusion: We observed no association of CGA prior to TAVI with POD incidence or postoperative self-care, highlighting the need for additional studies investigating the effect of POD preventive measures in older TAVI patients integrated into a comprehensive geriatric comanagement program.Keywords: POPS, frail older adults, perioperative care, aortic stenosis, TAVI, delirium